Early onset inflammatory bowel disease: manifestations, genetics and diagnosis - Moazzami, Bobak; Moazzami, Kasra; Rezaei, Nima (The Turkish Journal of Pediatrics, 2019)
Crohn`s disease and ulcerative colitis are immunologically mediated chronic inflammatory conditions, collectively referred to as inflammatory bowel diseases (IBD). While most studies have described the condition in the adult population, recent evidences suggest that IBD in children may represent an etiologically distinct disease from the adult onset IBD. Since a significant proportion of patients diagnosed with IBD demonstrate their clinical manifestations during childhood, knowledge about the disease progression, severity and diagnosis in this particular patient population is crucial. Therefore, in the present study, the clinical manifestations, recent advancements in the genetics of early onset IBD and the clinical approach to diagnoses of IBD in children are described.
Keywords: Crohn`s disease; inflammatory bowel diseases; interleukin-10